2018
DOI: 10.1089/jpm.2017.0503
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Pain and Functional Status in Patients with Amyotrophic Lateral Sclerosis: A Multicenter Cross-Sectional Study

Abstract: Our study indicates that all patients with ALS have the potential to suffer from pain, the intensity of which increases with decreased functional status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…The bivariate model shows that pain, depression, and anxiety affect physical and psychological QoL. Previous smaller studies have found comparable prevalence of pain in ALS: 53.8% in a multicentre study (n = 80) [36], 56.9% in a regional study (n = 160) [37], and 78-85% in two small clinic-based studies (n = 46 or n = 42) [38,39]. Those studies including a control group showed that pain in ALS/MND exceeded the population-based control rate [37][38][39].…”
Section: Discussionmentioning
confidence: 66%
“…The bivariate model shows that pain, depression, and anxiety affect physical and psychological QoL. Previous smaller studies have found comparable prevalence of pain in ALS: 53.8% in a multicentre study (n = 80) [36], 56.9% in a regional study (n = 160) [37], and 78-85% in two small clinic-based studies (n = 46 or n = 42) [38,39]. Those studies including a control group showed that pain in ALS/MND exceeded the population-based control rate [37][38][39].…”
Section: Discussionmentioning
confidence: 66%
“…The dreaded trouble of chronic disease is the pain which the participants of our research described as unbearable. Ishida et al 22 found out that among all patients with ALS, the pain worsened together with the deteriorated functional state. Adequate treatment of pain is one of the priorities of the palliative care.…”
Section: Discussionmentioning
confidence: 99%
“…The Barthel Index (BI) [46] is a valid instrument to measure physical disability and is frequently used in the context of rehabilitation [47]. It has also previously been used in ALS [48,49]. In this study, the functional status of the patient's during daily life was proxy-reported by the CG by using this measure.…”
Section: Patients' Functional Statusmentioning
confidence: 99%